Bevacizumab-treated pregnant rats may constitute an experimental model for studying preeclampsia - Boztosun, Abdullah; Olgan, Şafak; Özer, Hatice; Atilgan, Remzi; Pala, Şehmus (My University, 2018)
Purpose: To develop a rat model of preeclampsia by administering bevacizumab, an angiogenesis inhibitor.Materials and methods: Sixteen pregnant rats were randomly allocated to intraperitoneal injection of 10 mg/kgbevacizumab or 0.1 cc intraperitoneal serum physiologic on the 4th and 8th days of gestation. Blood pressure,body weight, and proteinuria were measured on both day 0 (D0) and day 20 (D20). Blood samples were collectedon D20 for analysis, including for determining vascular endothelial growth factor (VEGF) and soluble Fms-liketyrosine kinase 1 (sFlt-1) levels. On the same day, the mice were euthanized, the placentas and pups wereweighted, and the angiogenesis markers and microvessel density were evaluated using immunohistochemicalmethods.Results: Lower serum VEGF (p=0.038) and higher SFlt-1 (p=0.015) levels were observed in bevacizumabtreated pregnant rats. Bevacizumab-treated pregnant rats had significantly higher systolic (p=0.050) anddiastolic (p = 0.046) blood pressures compared to the controls. Additionally, the bevacizumab group showed asignificant increase in proteinuria on D20 compared to that on D0 (p=0.026). Although higher serum AST, ALT,BUN, and creatinine levels and renal glomerular endotheliosis scores as well as lower placental VEGF andmicrovessel density were noted in bevacizumab-treated rats, these differences were not statistically significant(p > 0.05 for each).Conclusion: The promising results of this trial show that bevacizumab treatment in pregnant rats might providea model to study human preeclampsia.
Keywords: Tıbbi Araştırmalar Deneysel; Kadın Hastalıkları ve Doğum